2020
DOI: 10.32942/osf.io/473pn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reported individual costs and benefits of sharing open data among Canadian academic faculty in ecology and evolution

Abstract: Open data facilitate reproducibility and accelerate scientific discovery but are hindered by perceptions that researchers bear costs and gain few benefits from publicly sharing their data, with limited empirical evidence to the contrary. We surveyed 140 faculty members working in ecology and evolution across Canada’s top 20-ranked universities and found that more researchers report benefits (47.9%) and neutral outcomes (43.6%) than costs (21.4%) from sharing data. Benefits were independent of career stage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Several surveys of data sharing practices show that less experienced researchers are hesitant to share data and analysis code out of fear of public shaming, loss of reputation, etc., if any errors are found (Meteyard & Davies, 2020;Soeharjono & Roche, 2021). It is possible that errors may be found, but this does not necessarily lead to an adverse effect on one's career (Ebersole et al, 2016).…”
Section: (Ir)reproducibility In Psychology and Psycholinguistics 21mentioning
confidence: 99%
“…Several surveys of data sharing practices show that less experienced researchers are hesitant to share data and analysis code out of fear of public shaming, loss of reputation, etc., if any errors are found (Meteyard & Davies, 2020;Soeharjono & Roche, 2021). It is possible that errors may be found, but this does not necessarily lead to an adverse effect on one's career (Ebersole et al, 2016).…”
Section: (Ir)reproducibility In Psychology and Psycholinguistics 21mentioning
confidence: 99%
“…We found no evidence to suggest that PI gender influences the quality of open data (Figs 2 , S2 A,B). This result is encouraging given that men in E&E selfidentify as experiencing more costs than women as a result of sharing open data 2 . Women accounted for almost half of the PIs assessed in our study, yet far fewer than 50% of PIs in biology departments at Canadian institutions identify as women 27 .…”
mentioning
confidence: 67%
“…Many journals, funding agencies, and policymakers agree that the societal benefits of publicly sharing (non-sensitive) research data outweigh any perceived or reported costs to individual researchers 2-6 . Indeed, while some researchers remain reluctant to share the data underlying their published results 3,7 , most view open data positively 2,8,9 . Since 2010, when a handful of journals began requiring open data in ecology and evolution (E&E) 10 , policies encouraging this practice have grown rapidly.…”
mentioning
confidence: 99%
See 2 more Smart Citations